Porous Silicon Covered with Silver Nanoparticles as Surface-Enhanced Raman Scattering (SERS) Substrate for Ultra-Low Concentration Detection. Issue 12 (December 2015) - Kosović, Marin; Balarin, Maja; Ivanda, Mile; Đerek, Vedran; Marciuš, Marijan; Ristić, Mira; Gamulin, Ozren
Microporous and macro-mesoporous silicon templates for surface-enhanced Raman scattering (SERS) substrates were produced by anodization of low doped p-type silicon wafers. By immersion plating in AgNO3, the templates were covered with silver metallic film consisting of different silver nanostructures. Scanning electron microscopy (SEM) micrographs of these SERS substrates showed diverse morphology with significant difference in an average size and size distribution of silver nanoparticles. Ultraviolet–visible–near-infrared (UV-Vis-NIR) reflection spectroscopy showed plasmonic absorption at 398 and 469 nm, which is in accordance with the SEM findings. The activity of the SERS substrates was tested using rhodamine 6G (R6G) dye molecules and 514.5 nm laser excitation. Contrary to the microporous silicon template, the SERS substrate prepared from macro-mesoporous silicon template showed significantly broader size distribution of irregular silver nanoparticles as well as localized surface plasmon resonance closer to excitation laser wavelength. Such silver morphology has high SERS sensitivity that enables ultralow concentration detection of R6G dye molecules up to 10 −15 M. To our knowledge, this is the lowest concentration detected of R6G dye molecules on porous silicon-based SERS substrates, which might even indicate possible single molecule detection.